(untitled) (American Journal of Islam and Society, 2001)
This is a book version of Kansu’s doctoral thesis, in which his objective "was to show [the political] transformation [in the beginning of the century]-however elusive- by re-telling the political history of modem Turkey in a radically different fashion" (p. ix). He states that this radical approach is based on an ’"historical’ viewpoint [which is) opposed to a ’political’ one"(p. ix). In order to show his radical re-telling of the political transformation of the Ottoman Empire in the beginning of the previous century, the book commences with a critical but analytical and enjoyable chapter on Turkish historiography by making special emphasis on the interpretation of the Revolution of 1908. In doing so, Kansu summarises the attitudes of the Turkish academics and intellectuals towards the interpretation of recent Turkish history. This in tum is an attempt to clarify his ideological stand as regards the Kemalist revolution of 1923 and the Young Turks. The first concept the reader encounters with the first chapter is ’Revolution’. For Kansu the year 1908 is the most crucial year in modem Turkish history, "because a new era opens before the Turkish social formation through a genuine revolutionary movement. 1908 is the beginning of the establishment -for the first time in modem Turkish history- a constitutional monarchical form of government which legitimates itself on the presence of a representative parliament to which it is totally responsible" (p. l). It has to be stated that while the "genuine revolutionary character" of the constitutional movement is open to question, Ottomans had the first parliamentary political structure not in 1908 but in 1876, albeit it lived only a short while due to Abdulhamid H’s political ambitions and, one has to accept, it was not as strong as the 1908 experience in its representation. However, Kansu claims that it was the ...